(untitled) (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: The research aimed to determine disability identity, athletic identity, and sports motivation of physically disabled people participating in physical activity and sports and to evaluate the influence of disability identity on physically disabled people’s athletic identity and sports motivation according to the level of participation in physical activity and sports. Hypothesis: A positive disability identity can lead to a higher athletic identity and greater motivation to participate in physical activity and sports. Methods: The Personal Disability Identity (PDI) scale including subscales of Self-Worth and Personal Meaning was used to assess self-concept as a person with a disability. Athletic identity was evaluated by the multidimensional Athletic Identity Measurement Scale to assess the social identity, exclusivity, and negative affectivity of the physically disabled. Sport Motivation Scale (SMS-II) including subscales of Intrinsic Regulation, Integrated Regulation, Identified Regulation, Introjected Regulation, External Regulation, and Non-Regulation was used to evaluate the reasons why physically disabled people are practising sports. The data were collected from 102 people with physical disabilities. Results: Findings indicated that scores on disability self-worth and personal meaning, athletic identity and sports motivation were significantly related (p < 0.005) after accounting for demographic and disability characteristics. Conclusion: The findings of the research on the relationship between positive adjustment among people with disabilities, their athletic identity and sports motivation contribute to the emerging literature on the predictive role of disability identity and the benefits of physical activity and sports in positive life outcomes among adults with physical disabilities. Support/Funding Source: The research was conducted using the author’s resources, without any financial support from external sources.